Perspektif Remaja di Medan terhadap Peran Komunikasi Keluarga dalam Kesehatan Mental - Lubis, Listya Nasyroh; Zuhdi, Abdurrahman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aimed to explore the perspectives of adolescents in Medan City towards the role of family communication in maintaining their mental health. Amid the pressures of urbanization, academic expectations, and digital disruption, family communication is a crucial aspect that is often overlooked. Using a qualitative approach with phenomenology methods, data were collected through in-depth interviews of eight adolescent informants, complemented by observation and documentation. Study results show that communication in families is often one-way, minimal in empathy, and does not open a safe space for teens to express themselves. This encourages them to seek emotional escapes outside of their homes, including social media and peer environments. Drawing on Carl Rogers’ communication theory, it was found that healthy communication should be built on a foundation of empathy, authenticity, and unconditional acceptance. This study recommends the importance of reconstructing more dialogical and supportive patterns of family communication so that the family again functions as a place of emotional recovery and mental strengthening for adolescents.